MITIGATION OF SOIL-TRANSMITTED HELMINTHIASES RESURGENCE IN THE ERA OF COVID-19 DISRUPTION: A LITERATURE REVIEW - Falah, Pilar Menara; Yani Corvianindya Rahayu; Atik Kurniawati; Yudha Nurdian (Majalah Biomorfologi, 2022)
Highlights: 1.    Prolonged interruptions and delays that accompany the COVID-19 pandemic have further increased the spread of STH in high-transmission areas.2.    Adaptations carried out in the context of a pandemic are able to strengthen efforts to sustain deworming programs based on primary health facilities and their integration into community-based platforms.3.    Community-based WASH activities must be continued by adjusting WASH messages to focus on preventing the transmission of COVID-19. Abstract: Background: Interruptions and postponements are influencing people's desire for soil-transmitted helminthiases (STH) services as all countries are fighting the Covid-19 pandemic. The risk of spreading STH in high-transmitting areas increases with increased disturbance. Indonesia is a compatible host country for STH because it is a tropical country. The STH impacts the population's nutrient status and disturbs their cognitive processes. Objective: To describe the issue and how best efforts had been made to mitigate the possibility of a resurgence of intestinal worms during the disruptions caused by the Covid-19 pandemic. Material and Method: Search for the most recent articles in a database of research in January 2022 on Google Scholar, Science Direct, and PubMed. Qualifying articles were then extracted and synthesized qualitatively. Discussion: The interference and postponement of the deworming control program due to COVID-19 had a tentative effect on the progress of achieving the elimination of STH as a public health problem by 2030. Conclusion: Best practices show that revitalization efforts to control STH by strengthening integrated interventions and collaborations through the expansion of POPM, PHBS, and STBM in line with COVID-19 prevention efforts with mitigation innovations shifting from controlling morbidity to terminate the transmission of STH.